Haptic perception of users with low vision and their needs in haptic-incorporated user interfaces. (23rd April 2013) - Kim, Hyung Nam; Smith-Jackson, Tonya; Terpenny, Janis
Abstract: Purpose : This paper reports on research aimed at advancing understanding haptic capability and needs of users with low vision. The objective is to apply this understanding to the design of haptic-incorporated user interfaces. Method : Study 1 investigated the haptic perception between sighted participants and those with low vision through the magnitude estimation technique, and Study 2 explored the degree to which similar user interface needs were observed among the two vision groups. Results : Overall, our findings indicate there was no significant difference between the two vision groups in terms of haptic perception and user interface needs. A few differences in user interface preference did exist, however, and designers should take these into account. Conclusions : Participants with low vision were a group who relied on their vision in everyday life instead of touch. Thus, their haptic capability was less likely to be enhanced via brain plasticity, which probably contributed to no significant difference in haptic-incorporated user interface needs. Implications for Rehabilitation: No significant different haptic capability and haptic user interface (UI) needs exists between cited participants and those with low vision. UI designers should take into consideration that a certain range of magnitude/type of haptic feedback is available to accommodate preferences of both vision groups, which would ultimately increase the likelihood of successfully developing universal designs.